PENINGKATKAN AKTIVITAS DAN HASIL BELAJAR MATEMATIKA DALAM PEMBELAJARAN BERBASIS KECERDASAN VISUAL SPASIAL - Isna Purti Astuti (Malih Peddas (Majalah Ilmiah Pendidikan Dasar), 2015)
This research is a class act who has a goal to increase the activity and mathematics learning outcomes was the specific goal is Improving Mathematics activity and learning outcomes in Visual Spatial Intelligence Based Learning material opportunities for students of class IX B SMP Negeri 2 Jiken the school year 2014/2015.The research was done in SMP N 2 Jiken class IX and the number of 30 students. Done with 2 cycles, 1 cycle starts with planning, action, observation and refeksi or analyzes that compare the test results with the initial condition of the test results in cycle 1. Similarly for Cycle 2 with reflection study comparing the results with the results of the test cycle 1 to cycle test 2.From the learning outcomes of students who completed at cycle 2 looks 83,3 More learning outcomes of students who pass the initial conditions (20%) to siklus1 (60%) an increase of 40%, while learning completeness of the initial conditions (20%) to cycle 2 (83.33%) an increase of 63.33%. The average value of students also increased from the prior actions or initial conditions (55) to Cycle 1 (58.19) or up to 3.19 while the average of cycle 1 (58.19) to cycle 2 (63.61) rises 5.42 while the average of the initial conditions (55) to siklus2 (63.61) is also an increase of 8.61.There was an increase in all indicators of initial conditions to cycle 2. Learn to indicators of the presence of initial conditions (63.33%) 2 cycles (83.337%) an increase of 20%, listening to the teacher's explanation of the initial conditions (33.33%) cycle 2 (73.33%) an increase of 40%, do the exercise of the teacher of initial conditions (30%) 2 cycles (66.67%) an increase of 36.67%, a discussion with a friend in the group of initial conditions (26.67%) cycle 2 (76.67%) an increase of 50%, an indicator makes the homework of the initial conditions (23.33%) 2 cycles (60%) increased 46.67%, presented the results of the discussion of the initial conditions (33.33%) 2 cycles (90%) an increase of 56.67%.